ANALISIS KESALAHAN EJAAN DALAM KARANGAN SISWA PADA MATA PELAJARAN BAHASA INDONESIA KELAS IV SEKOLAH DASAR - Dwi Yanti; Hetilaniar Hetilaniar; Susanti Faipri Selegi (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
Writing essays is one of the writing skills taught to grade IV students at SD Negeri 26 Talang Kelapa. However, many spelling mistakes were still found in students' writings. For this reason, the problem in this study was the spelling mistakes found in students' essays in Indonesian subject at grade IV of elementary schools. The purpose of this study was to describe the spelling mistakes found in students' essays in Indonesian subjects at grade IV of elementary school. The object of this study was the spelling mistakes found in the students' essays. The informants in this study were students and teachers of class IV SD Negeri 26 Talang Kelapa Kabupaten Banyuasin. This research utilized a qualitative descriptive method. Data were collected through documentation and interviews. The data were analyzed through data reduction, data presentation, and conclusion drawings. The results of this study indicated that the mistakes were in using capital letters, fullstop, commas, and pronouns. This is because students did not understand the right spelling in writing. The students had difficulties in writing essays since they paid less attention to the teacher's explanations in Indonesian subjects. Thus, the teacher needed to improve students' understanding of the use of spelling.